2017
DOI: 10.1371/journal.pone.0173499
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non-alcoholic fatty liver disease and risk factors for advanced fibrosis and mortality in the United States

Abstract: In the United States, non-alcoholic fatty liver disease (NAFLD) is the most common liver disease and associated with higher mortality according to data from earlier National Health and Nutrition Examination Survey (NHANES) 1988–1994. Our goal was to determine the NAFLD prevalence in the recent 1999–2012 NHANES, risk factors for advanced fibrosis (stage 3–4) and mortality. NAFLD was defined as having a United States Fatty Liver Index (USFLI) > 30 in the absence of heavy alcohol use and other known liver disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
216
4
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(235 citation statements)
references
References 32 publications
10
216
4
5
Order By: Relevance
“…However, adjusting for multiple risk factors eliminated these statistically significant associations (Figures A‐D). In a recent report using the NHANES 1999‐2012 population, a high US FLI was associated with increased overall mortality but only among participants with a high probability of fibrosis suggesting the importance of a multifaceted approach including steatosis for risk stratification in patient care and surveillance strategies . Follow‐up was not of sufficient length to investigate disease‐specific mortality outcomes in that survey, as compared to NHANES III with up to 27 years of linked‐mortality data recently made available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, adjusting for multiple risk factors eliminated these statistically significant associations (Figures A‐D). In a recent report using the NHANES 1999‐2012 population, a high US FLI was associated with increased overall mortality but only among participants with a high probability of fibrosis suggesting the importance of a multifaceted approach including steatosis for risk stratification in patient care and surveillance strategies . Follow‐up was not of sufficient length to investigate disease‐specific mortality outcomes in that survey, as compared to NHANES III with up to 27 years of linked‐mortality data recently made available.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report using the NHANES 1999-2012 population, a high US FLI was associated with increased overall mortality but only among participants with a high probability of fibrosis suggesting the importance of a multifaceted approach including steatosis for risk stratification in patient care and surveillance strategies. 42 Non-alcoholic fatty liver disease is widely considered associated with an increased risk of fatal and nonfatal cardiovascular disease, although the causal relationship is not clear. 1,12,43 The lack of an association of increased cardiovascular disease mortality with higher levels of liver fat scores in this study should be interpreted with caution due to the significant overlap of these metabolic disorders.…”
Section: Fat Scores and Liver Disease Mortalitymentioning
confidence: 99%
“…Epidemiologically, NAFLD and NASH are very common conditions. The prevalence of NAFLD in the 1999-2012 National Health and Nutrition Examination Survey (NHANES) was 30% in the 6,000 included subjects and 10.3% of them presented advanced fibrosis [48]. Of note, the same study also demonstrated an increased risk of mortality associated with advanced fibrosis.…”
Section: Nutrition Assessment In Specific Etiologies Of Liver Diseasementioning
confidence: 99%
“…The prevalence of NAFLD is estimated to be at 30% in the United States 2 and up to 45% in Asia. 3 Based on the rapid increases in fatty liver disease, NAFLD/NASH is expected to replace viral hepatitis as the leading cause of cirrhosis; NAFLD is already the most common chronic liver disease worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…3 Because of the rapid increases in fatty liver disease, NAFLD/NASH is expected to replace viral hepatitis as the leading cause of cirrhosis; NAFLD is already the most common chronic liver disease worldwide. 2,4 HCC can occur as a sequela to NASH or on account of chronic infection with hepatitis B virus (HBV), hepatitis C virus, or a combination of the two. In the United States, HCC is responsible for the highest annual percentage increases in mortality rates-2.8% for males and 2.1% for females-in comparison with all other cancer sites, whose rates have decreased by 1.8% for males and 1.4% for females.…”
Section: Introductionmentioning
confidence: 99%